Highly Sensitive Filter Paper Substrate for SERS Trace Explosives Detection. (17th October 2012) - Fierro-Mercado, Pedro M.; Hernández-Rivera, Samuel P.
Abstract : We report on a novel and extremely low-cost surface-enhanced Raman spectroscopy (SERS) substrate fabricated depositing gold nanoparticles on common lab filter paper using thermal inkjet technology. The paper-based substrate combines all advantages of other plasmonic structures fabricated by more elaborate techniques with the dynamic flexibility given by the inherent nature of the paper for an efficient sample collection, robustness, and stability. We describe the fabrication, characterization, and SERS activity of our substrate using 2, 4, 6-trinitrotoluene, 2, 4-dinitrotoluene, and 1, 3, 5-trinitrobenzene as analytes. The paper-based SERS substrates presented a high sensitivity and excellent reproducibility for analytes employed, demonstrating a direct application in forensic science and homeland security.